2020
DOI: 10.1002/mus.26864
|View full text |Cite
|
Sign up to set email alerts
|

Fasciculations demonstrate daytime consistency in amyotrophic lateral sclerosis

Abstract: Introduction: Fasciculations represent early neuronal hyperexcitability in amyotrophic lateral sclerosis (ALS). To aid calibration as a disease biomarker, we set out to characterize the daytime variability of fasciculation firing.Methods: Fasciculation awareness scores were compiled from 19 ALS patients. In addition, 10 ALS patients prospectively underwent high-density surface electromyographic (HDSEMG) recordings from biceps and gastrocnemius at three time-points during a single day.Results: Daytime fascicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Fermont showed that fasciculations occur frequently in the lower leg muscles of healthy people and may be temporarily increased by physical exercise (Fermont et al, 2010), with the theory being that exercise may induce this increase via metabolic stress. The gastrocnemius has also shown more diurnal variation in FP frequency than the BB (Bashford et al, 2020a), suggesting values recorded in the gastrocnemius may be more sensitive to the exact timing of HDSEMG recording than in BB. Furthermore, fasciculations in ALS patients have been shown to occur more often in proximal than in distal muscles, and markedly more frequently in the upper than in the lower limbs (Krarup, 2011), further promoting the use of BB or other upper limb muscles in the future assessment of the utility of HDSEMG in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Fermont showed that fasciculations occur frequently in the lower leg muscles of healthy people and may be temporarily increased by physical exercise (Fermont et al, 2010), with the theory being that exercise may induce this increase via metabolic stress. The gastrocnemius has also shown more diurnal variation in FP frequency than the BB (Bashford et al, 2020a), suggesting values recorded in the gastrocnemius may be more sensitive to the exact timing of HDSEMG recording than in BB. Furthermore, fasciculations in ALS patients have been shown to occur more often in proximal than in distal muscles, and markedly more frequently in the upper than in the lower limbs (Krarup, 2011), further promoting the use of BB or other upper limb muscles in the future assessment of the utility of HDSEMG in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…(62). They also used this non-invasive tool to characterise daytime fasciculation activity, something that would be unpleasant for patients with needleelectromyogram (63). Another non-invasive technique is the motor unit size index (MUSIX), a surrogate for reinnervation derived from CMAP and MUNIX.…”
Section: Imagingmentioning
confidence: 99%